2015
DOI: 10.1002/hbm.22737
|View full text |Cite
|
Sign up to set email alerts
|

Genetic contribution of catechol‐O‐methyltransferase in hippocampal structural and functional changes of female migraine sufferers

Abstract: Physiological and emotional stressors are associated with or provoke each migraine attack and cause structural and functional changes in the central nervous system. The hippocampus, a limbic structure important in anxiety-related behavior, is vulnerable to long-term stress. Given that catechol-O-methyltransferase (COMT) is widely distributed in the hippocampus and its genetic variation is thought to contribute to the interindividual variability in pain perception and anxiety regulation, whether or not migraine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…In addition, patients with dysmenorrhea demonstrate greater menstrual-related increases in primary somatosensory cortex gray matter volume compared to female healthy controls (Tu et al 2013). Furthermore, additional primary sensorimotor cortical alterations including connectivity, intrinsic activity, reactivity, and perfusion have been noted in female-specific chronic pain studies (Arkink et al 2012; Burgmer et al 2012; Ellingson et al 2012; Guedj et al 2008; Guedj et al 2007; Gupta et al 2015; Kamping et al 2013; Kilpatrick et al 2014; Kim et al 2013; Lee et al 2013; Liu et al 2015a; Liu et al 2015b; Pujol et al 2014; Rahm et al 2015; Tu et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients with dysmenorrhea demonstrate greater menstrual-related increases in primary somatosensory cortex gray matter volume compared to female healthy controls (Tu et al 2013). Furthermore, additional primary sensorimotor cortical alterations including connectivity, intrinsic activity, reactivity, and perfusion have been noted in female-specific chronic pain studies (Arkink et al 2012; Burgmer et al 2012; Ellingson et al 2012; Guedj et al 2008; Guedj et al 2007; Gupta et al 2015; Kamping et al 2013; Kilpatrick et al 2014; Kim et al 2013; Lee et al 2013; Liu et al 2015a; Liu et al 2015b; Pujol et al 2014; Rahm et al 2015; Tu et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a specific involvement of these regions has been demonstrated in migraine patients with anxiety or depression. Functional alterations of the hippocampus (Liu et al, 2015 ) and thalamus (Wei et al, 2019 ) have been associated with the presence of anxiety in patients with migraine. Using diffusion tensor imaging, a technique that allows exploring the microstructure of brain WM tracts in vivo , Li and colleagues (Li et al, 2011 ) have shown alterations of the corpus callosum in migraine patients with anxiety or depressive disorder.…”
Section: Migraine Comorbidity As Judged By Neuroimaging Techniquesmentioning
confidence: 99%
“…2-ME is synthesized by hydroxylation and subsequent O-methylation catalyzed by catechol-O-methyltransferase (COMT) [11,12]. COMT is widely distributed in the hippocampus where it catabolizes the catecholamine neurotransmitters and influences cognitive function, regulates dorsal hippocampal neurochemistry, and modulates hippocampusdependent behaviors [13,14]. Thus, 2-ME may be a metabolite of E2 also in brain structures.…”
Section: Introductionmentioning
confidence: 99%